City of night - West, Michelle (New York : Dow Books Inc, 2010)
As Rath joins with mages and the Twin Kings' agents to wage a secret battle against the Lord of the Hells and his servants, he gives Jewel Markess and her den of orphans the opportunity to escape the chaos by providing them with a note of introduction to the head of House Terafin, where Jewel will discover her destiny
Keywords: Demonology -- Fiction; Orphans -- Fiction; Good and evil -- Fiction; Imaginary wars and battles -- Fiction; Magic -- Fiction